A proposed education, outreach and promotion program for Ellen G. White Archives and Research Center, SDA in Cavite, Philippines - Wamalika, Martha C.; Gonzales, Grace Marie B.; Montesa, Teresa S. (Quezon City Institute of Library and Information Science, University of the Philippines Diliman, 2006)
Promotion which is one of the principles of archives still remains a challenge to most of the archives centers today. This study focused on a church archives, EGWARC, in the Philippines, under the Seventh Day Adventist church. The Center is a branch of the Ellen G. White Estate in Maryland, USA. It serves as a special resource on the life and works of Ellen G. White, SDA history and theology to the countries in Asia Pacific. It houses copyrights of thousands of manuscripts and publications. The target groups comprised of a sample of ninety-three (93) leaders, professors/lecturers, seminarians/pastors and graduate students from Southern Asia region.
The results showed that the Center has ineffective promotion and outreach program that does not cover promotional needs of the Center. The users are not sure of the location of the Center, user attendance is decreasing and researchers are not well informed about the services available. The Center has no newsletter, brochure, posters and flyers. There are not outreach activities like open house, anniversaries, and even exhibition.
In concluding, an outreach program that promotes the relationship between EGWARC with her sponsors and users was proposed. It's also recommended to hire a webmaster who will create a detailed website, make use of scholarship as a reward system, and promote the Center to its sponsors.
Vita.
Thesis (Master of Library and Information Science)
Keywords: Seventh Day Adventist Church -- Archival resources; Church archives -- Philippines -- Cavite -- Administration